Floristic Inventory of The Proposed Site for Tarsier Tourism Center in Villa Aurora, Bilar, Bohol, Philippines - Tomas D Reyes Jr; Jeralyn D Abadingo; Shiela G Tabuno; Eunice K L Serino; Joecel B Mabanag; Rizaldy C Merdacal (Fakultas Kehutanan Universitas Gadjah Mada, 2015)
The study assessed the present vegetation composition of the Proposed Site for the Tarsier Tourism Center (PTTC) at Villa Aurora, Bilar, Bohol and performed a comparative analysis with the existing Tarsier Sanctuary (TS) at Canapnapan, Corella, Bohol. The basis for comparison was the computed importance values, species richness, species dominance, and percent distribution of plants according to self-defined DBH classes. Results showed that both sites had very high species richness and evenness values. Common overstorey and understorey plant species found in both areas were katagpo (Psychotria sp.), sagimsim (Syzygium brevistylum [C. B. Rob]Merr.) and bagauak (Clerodendrum minahassae Teijsm. & Binn.). Apart from sagimsim (Syzygium brevistylum [C.B.Rob.] Merr.), selaginella (Selaginella cuppresina Lin.), and lunas (Lunasia amara Blanco) were also common in the ground vegetation of both areas. Percent distribution of trees according to self-defined DBH classes revealed that PTTC had 87.55% of the total recorded plants with DBH measurements of <10 cm. Our data was found lower by almost 10% from TS. Considerable percentages of trees were also shared in other DBH classes for PTTC. DBH class range of 10-20 cm had 6.88%, while 5.58% was computed for DBH class of >20 cm. Percent distribution of trees on these DBH ranges (especially on DBH class >20 cm) indicated the presence of medium and large trees. The largest DBH measured in the PTTC was 70 cm while in TS was only 22 cm. The proposed 10-ha site in Villa Aurora, Bilar, is suited to be utilized as Tarsier Tourism Center. In case the proposed project is to be pursued, enclosure similar to what has been constructed in Canapnapan, Corella, Bohol, Philippines should also be established to prevent stray animals from predating the captive tarsiers.Keywords: floristic inventory, Philippine tarsier, Bohol, primate conservation, tourism. Inventarisasi flora dari Situs Usulan untuk Sentra Wisata Tarsier di Villa Aurora, Bilar, Bohol, FilipinaAbstractPenelitian ini ditujukan untuk melakukan penilaian komposisi vegetasi dari Usulan Lokasi Pusat Wisata Tarsius (ULPWT) di Villa Aurora, Bilar, Bohol dan melakukan analisis perbandingan antara Tarsier Sanctuary (TS) yang ada di Canapnapan, Corella, Bohol. Dasar perbandingan yang digunakan yaitu dengan menghitung nilai penting, kekayaan spesies, dominansi spesies, dan prosentase distribusi dari tumbuhan berdasarkan kelas diameter yang telah ditentukan. Hasil penelitian menunjukkan bahwa kedua tempat memiliki kekayaan spesies dan nilai evenness/ kemerataan yang sangat tinggi. Spesies tumbuhan yang umum ditemukan di overstorey dan understorey di kedua area adalah katagpo (Psychotria sp.), sagimsim (Syzygium brevistylum [C. B. Rob]Merr.), dan bagauak (Clerodendrum minahassae Teijsm. & Binn.). Selain itu, sagimsim (Syzygium brevistylum [C.B.Rob.] Merr.), selaginella (Selaginella cuppresina Lin.), dan lunas (Lunasia amara Blanco) juga umum ditemukan di lantai hutan di kedua tempat. Prosentase distribusi dari tumbuhan berdasarkan kelas diameter yang telah ditentukan menunjukkan bahwa ULPWT memiliki 87.55% dari keseluruhan tumbuhan yang tercatat dengan ukuran diameter <10 cm. Data kami menunjukkan bahwa nilai tersebut lebih rendah 10% dari TS. Sebagian persentase dari pohon juga dimiliki di ULPWT pada kelas diameter lainnya. Kelas diameter 10-20 cm memiliki 6,88%, sementara 5,58% terhitung untuk kelas diameter >20 cm. Prosentase distribusi dari pohon pada kisaran ini (khususnya pada diameter >20 cm) menunjukkan adanya kehadiran pohon berukuran medium dan besar. Diameter terbesar yang terukur di ULPWT adalah 70 cm sementara di TS hanya sebesar 22 cm. Lokasi seluas 10 ha di Villa Aurora, Bilar, sesuai untuk digunakan sebagai Pusat Wisata Tarsius. Apabila akan didirikan, maka kandang yang dibangun diharapkan mirip dengan yang telah dibangun di Canapnapan, Corella, Bohol, Pilipina, agar mencegah pemangsaan oleh satwa yang lepas.